2009
DOI: 10.1002/car.1084
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and child abuse: a child‐centred perspective

Abstract: A substantial body of literature assessing the impact of intimate partner violence on children and associations between intimate partner violence and child abuse now exists. Central to knowledge about these areas of practice and research is a robust, child-centred consideration of some of the more challenging conceptual issues they give rise to. In this paper, we aim to stimulate debate by presenting a critical, child-centred perspective on the intersection between intimate partner violence and child abuse. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 62 publications
1
22
0
6
Order By: Relevance
“…The presence of IPV in the family increases the risk that children will in turn be the direct victims of maltreatment [29][30][31][32][33][34]. Several studies have shown that exposure to both IPV and direct CM has an even more deleterious effect on children's adaptation [16,17,35,36].…”
Section: Consequences For Children Of Being Exposed To Intimate Partnmentioning
confidence: 99%
“…The presence of IPV in the family increases the risk that children will in turn be the direct victims of maltreatment [29][30][31][32][33][34]. Several studies have shown that exposure to both IPV and direct CM has an even more deleterious effect on children's adaptation [16,17,35,36].…”
Section: Consequences For Children Of Being Exposed To Intimate Partnmentioning
confidence: 99%
“…Research focused on the extent of the co-occurrence of wife abuse and child corporal punishment has found high rates of overlap between intimate partner violence and child maltreatment and abuse (Goddard & Bedi, 2010;Straus, 2010). Tajima (2000Tajima ( , 2004 found wife abuse to be a consistent risk factor for all forms of violence against children including abuse, physical punishment, and verbal abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Toutefois, les rapports de pouvoir ne caractérisent pas tous les types de violence au sein de la famille, certains pouvant découler davantage du stress ou des conditions de vie difficiles auxquels sont confrontés les parents (Sprang et al, 2005 ;Stith et al, 2011) ou l'aidant naturel dans le cas des personnes âgées (Roberto et al, 2013). Le fait d'étudier les liens entre les violences conjugales et d'autres formes de violence familiale permet de prendre en considération les nombreuses situations où les violences se présentent de manière concomitante au sein d'une même famille (Chang et al, 2011 ;Finkelhor et al, 2011 ;Goddard et Bedi, 2010 ;Clément et al, 2013 ;Margolin et al, 2009). Ces violences concernent tous les membres de la famille : les femmes, les hommes et les enfants exposés à la violence conjugale.…”
Section: En Quoi Les Connaissances Sur Les Violences Familiales Et Stunclassified